A Detailed Investigation Into the Wave Energy Resource at a Small-Scale Ocean Energy Test Site in China - Fang, Yizhou; Wu, He; Zhou, Qingwei; Jiang, Bo; Wang, Xiaoyong (Frontiers in Energy Research, 2022)
During the R&D of marine renewable energy converters, it is essential to carry out both laboratory and open sea tests to validate the feasibility and reliability. Due to cost constraints, a scale model is usually used in the early stages of development. China’s National Ocean Integrated Test Site is being developed by National Ocean Technology Center (NOTC) in Weihai, Shandong Province, to facilitate testing of scaled wave and tidal energy converters in an open sea environment. This research aims to gain a detailed understanding of wave characteristics and wave energy resource at this site. A coupled modelling system has been implemented using Simulating WAves Nearshore (SWAN) to provide a 10-year high-resolution wave hindcast between 2009 and 2019 with an approximate 60 m resolution covering the test site. The model has been validated against observation data. We analyzed the spatial and temporal distribution of seasonal averaged significant wave height, mean wave period, main wave direction and wave energy density. A strong seasonal variation in wave energy resource due to the monsoon system has been found. We also performed statistical analysis of the high and extreme wave conditions and its occurrence. The results of this study provide engineering references for the design of scale wave energy converter models which target to perform open sea tests in the National Small-scale test site.